The role of women in the fight against corruption in Ghana. Issue 4 (19th May 2021) - Kasser-Tee, Clara
ABSTRACT: This viewpoint discusses the role of women in the fight against corruption in Ghana. It argues that although there is no evidence that women in Ghana by their nature are less corrupt than men, gender parity presents an opportunity for women to be change agents in creating, nurturing, implementing, and enforcing systems, institutions, and values that sanction as well as disdain corrupt behaviour, provided that gender parity is linked with the creation of systems that limit opportunity for and sanction corruption, as well as the creation and sustenance of societal values that abhor corrupt behaviour.